Ou comme ça, machin et autres marqueurs d’indétermination dans les listes - Marie-José Béguelin; Gilles Corminboeuf (Discours)
This article deals with two extension particles (or “general extenders”) found in the OFROM corpus (French spoken in Switzerland). On the one hand, we study the sequence ou comme ça (“or like that”), whose high frequency seems to be characteristic of the OFROM corpus. On the other hand, we study the noun machin (“thingy”, “whatsit”), which is more uniformly spread in contemporary European spoken French. The examples studied are of the following types :[1] certaines se maquillent déjà ou bien mettent des robes ou euh + des ba- justement des chaussures un peu féminines comme des ballerines ou comme ça(unine11-csa)[2] je lui ai donné un millier de conseils va voir un psy va voir euh prends-toi en main fais quelque chose euh machin(unine08-vwa)The research is not limited to enumerative contexts. We examine all the uses of ou comme ça and machin in the OFROM data. We study their semantic functions, the type of vagueness they are associated with, and the way in which they come to assume comparable pragmatic functions at the end of the list. We highlight the morphosyntactic contexts that favor a reinterpretation of the name machin as an extension particle, or as a vagueness marker.